2020
DOI: 10.18178/ijesd.2020.11.2.1233
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Hydrological Drought Indicator for Tropical Drought Identification

Abstract: Drought's frequency, duration and severity are essentials for impact control and mitigation of droughts. This paper adopts 3-month seasonal scale Streamflow Drought Index (SDI-3) to analyze these drought characteristics for the tropical climate at the Central, Southern and East Coast regions of Peninsular Malaysia in 1997-2016. The identified drought events were then evaluated using four major historical events from five different locations. The results showed that SDI-3 identified the occurrences of all repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The most severe hydrological drought is occurred at station S21, located along the Bernam River, Selangor, in 1997-1998 According to Shaaban and Low (2003) 1997/1998 El-Nino drought event, particularly in Selangor districts and the Central region, and the effect lasted until September (Shaaban and Low, 2003). When comparing the 1997/1998 El-Nino to the 2015/2016 El-Nino drought, Fung et al (2020) discovered that high temperatures impacted the dry months in these times (Fung et al, 2020).…”
Section: Sdi Analysismentioning
confidence: 99%
“…The most severe hydrological drought is occurred at station S21, located along the Bernam River, Selangor, in 1997-1998 According to Shaaban and Low (2003) 1997/1998 El-Nino drought event, particularly in Selangor districts and the Central region, and the effect lasted until September (Shaaban and Low, 2003). When comparing the 1997/1998 El-Nino to the 2015/2016 El-Nino drought, Fung et al (2020) discovered that high temperatures impacted the dry months in these times (Fung et al, 2020).…”
Section: Sdi Analysismentioning
confidence: 99%
“…The future rainfall in several states in Malaysia is predicted to decrease due to climate change (Law and Bustami, 2013). In Malaysia, the spatial analysis study showed that most of the areas are more prone to a short term of drought and higher severity, especially at the north part of the Central Region and Southern Region and central part of the East Coast (Fung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…findings is consistent with to the results reported byShaaban and Low (2003), which concluded that Peninsular Malaysia was severely affected by the 1997/1998 El-Nino drought, especially in Selangor and central region, and the impact lasted until September 1998. Comparing the 1997/1998 El-Nino drought with the 2015/2016 El-Nino drought,Fung et al (2020) found that high temperatures affected the dry months during these periods.SDI results in the study region show that moderate and severe drought events follow each other for more than one year on average. For example, moderate drought occurred in 2012 and 2013.…”
mentioning
confidence: 99%